Oropharyngeal Colostrum Administration in Very Low Birth Weight Infants: A Randomized Controlled Trial - Zhang, Y.; Ji, F.; Hu, X.; Cao, Y.; Latour, Jos (Lippincott Williams & Wilkins, 2017)
Objectives: Studies have confirmed the safety of oropharyngeal administration of colostrum in very low birth weight infants. However, the effect of oropharyngeal administration of colostrum on immune system is inconclusive. This study aims to evaluate the effect of oropharyngeal administration of colostrum on secretory immunoglobulin A and lactoferrin in very low birth weight infants. DESIGN:: Randomized controlled trial. Setting: Forty-bedded neonatal ICU in a university children’s hospital in the People’s Republic of China. Patients: Very low birth weight infants were allocated to the study group (n = 32) and control group (n = 32). Intervention: The intervention was oropharyngeal administration of 0.2 mL of their mother’s colostrum every 4 hours for 7 days. The control group received saline solution. Measurements and Main Results: Secretory immunoglobulin A and lactoferrin in urine and saliva were measured within 24 hours of life (baseline) and at 7 and 21 days. Primary outcomes were changes of secretory immunoglobulin A and lactoferrin in urine and saliva between baseline and at 7 and 21 days. Infant’s clinical data were also collected during hospitalization. Change from baseline in lactoferrin in saliva at 7 days (5.18 ± 7.07 vs –1.74 ± 4.67 µg/mL; p < 0.001) and 21 days (5.31 ± 9.74 vs –1.17 ± 10.38 µg/mL; p = 0.02) shows statistic difference. No differences were found of lactoferrin in urine and also no differences of secretory immunoglobulin A in urine and saliva. There were also no differences between days to full enteral feeding, occurrence rate of clinical sepsis, proven sepsis, and necrotizing enterocolitis. Conclusions: Oropharyngeal administration of colostrum can increases the level of lactoferrin in saliva in very low birth weight infants. No effect could be documented of secretory immunoglobulin A and lactoferrin in urine. Larger trials are needed to better describe the benefit of oropharyngeal administration of colostrum, if any, in very low birth weight infants.